A nonrandomized, single-arm confirmatory trial of expanded endoscopic submucosal dissection indication for undifferentiated early gastric cancer: Japan Clinical Oncology Group study (JCOG1009/1010) - Takizawa, Kohei; Ono, Hiroyuki; Hasuike, Noriaki; Takashima, Atsuo; Minashi, Keiko; Boku, Narikazu; Kushima, Ryoji; Katayama, Hiroshi; Ogawa, Gakuto; Fukuda, Haruhiko; Fujisaki, Junko; Oda, Ichiro; et al. (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2021)
Background While endoscopic submucosal dissection (ESD) is recognized as a minimally invasive standard treatment for differentiated early gastric cancers (EGCs), it has not been indicated for undifferentiated EGC (UD-EGC) because of a relatively high risk of lymph node metastasis (LNM). However, patients with surgically resected mucosal (cT1a) UD-EGC ≤ 2 cm in size with no lymphovascular invasion or ulceration are reported to be at a very low risk of LNM. This multicenter, single-arm, confirmatory trial was conducted to evaluate the efficacy and safety of ESD for UD-EGC. Methods The key eligibility criteria were endoscopically diagnosed cT1a/N0/M0, single primary lesion, size ≤ 2 cm, no ulceration and histologically proven components of undifferentiated adenocarcinoma on biopsy. Based on the histological findings after ESD, additional gastrectomy was indicated if the criteria for curative resection were not satisfied. The subjects of the primary analysis were patients with UD-EGC as the dominant component. The primary endpoint was 5-year overall survival (OS) of patients with UD-EGC. Results Three hundred 46 patients were enrolled from 49 institutions. The proportion of en bloc resection was 99%. No ESD-related Grade 4 adverse events were noted. Delayed bleeding and intraoperative and delayed perforation occurred in 25 (7.3%), 13 (3.8%), and 6 (1.7%) patients, respectively. Among the 275 patients who were the subjects of the primary analysis, curative resection was achieved in 195 patients (71%), and 5-year OS was 99.3% (95% CI: 97.1–99.8). Conclusions ESD can be a curative and less invasive treatment for UD-EGC for patients meeting the eligibility criteria of this study.